The Effect of Financial and Non-financial Supports on the Productivity of MSEs in Indonesia - Cahyo Aji Widodo; Benedictus Raksaka Mahi (Universitas Hayam Wuruk Perbanas, 2022)
Micro and Small Enterprises (MSEs) contribute significantly to the economy and job creation. The majority of MSEs use simple or traditional technology in the production process. Several common obstacles cause low MSEs productivity, such as low-quality human resources, lack of knowledge, and difficulty in finance access. Various support programs have been implemented to help MSEs increase productivity. This research was conducted to provide empirical evidence of the effect of financial and non-financial support on the labor productivity of MSEs using data at the micro level. By using multiple linear regression for the cross-sectional data, this study concludes that groups of business units receiving financial support, non-financial support, and both forms of support at the same time have productivity of respectively 28.12 percent, 16.04 percent, and 6.36 percent, higher than those receiving no support at all. The results of this study also show that non-financial support has a higher impact on business units with larger sizes and business units with more prolonged operations. Due to their positive effect on productivity, assistance support programs must be extended to more business units. The implication of this research for business is that to provide optimal benefits, support programs should be tailored to the needs of each business unit.